1989
DOI: 10.1046/j.1468-2982.1989.0904239.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pressor Hyperresponsiveness to Phenylephrine Unmasks Sympathetic Hypofunction in Migraine

Abstract: The pressor responsiveness to phenylephrine, an almost pure agonist of peripheral alpha-1-adrenoceptors, was studied in 32 migraine patients in headache-free intervals. Eighteen healthy volunteers served as a control group. Fourteen patients and 14 controls also underwent the tilt test. The following observations were made: (1) the pressor response to phenylephrine was significantly greater and longer lasting in patients than in controls; (2) the reflex decrease of heart rate did not differ in the two groups; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…2 Studies have demonstrated an impairment of central monoaminergic systems in migraine. [3][4][5][6][7] These results suggest similar defects in central monoaminergic systems in tension-type headache, The coexistence of depression and tension headache is frequent. Depression could possibly be reactive to the headache syndrome, but a biologic connection between the two disorders may be a more important factor.…”
Section: Introductionmentioning
confidence: 79%
“…2 Studies have demonstrated an impairment of central monoaminergic systems in migraine. [3][4][5][6][7] These results suggest similar defects in central monoaminergic systems in tension-type headache, The coexistence of depression and tension headache is frequent. Depression could possibly be reactive to the headache syndrome, but a biologic connection between the two disorders may be a more important factor.…”
Section: Introductionmentioning
confidence: 79%
“…Some studies reported SNS hyperactivity, [3][4][5]9,10,17 while others reported SNS hypoactivity. 6,8,[13][14][15][18][19][20][21] All these studies were performed between migraine attacks. Two of the studies performed during a migraine attack reported hypoactivity 11,12 and one study reported hyperactivity of the SNS.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies, which have been performed on adult migraine in particular, are controversial. Some studies have reported normal ANS function, 1 , 2 whereas others have reported sympathetic nervous system (SNS) dysfunction 3 –17 or both SNS and parasympathetic nervous system dysfunction 18 –21 . Studies regarding ANS function in childhood migraine are limited 22 .…”
mentioning
confidence: 99%
“…Alpha‐adrenergic receptor supersensitivity has also been demonstrated in migraineurs by injecting the α‐adrenergic agonist, phenylephrine. The pressor response to an intravenous injection of 100 μg phenylephrine was significantly greater, as well as more prolonged, in migraineurs versus controls 13 . Phenylephrine increased systolic and diastolic BPs, the mean arterial pressures, and heart rate significantly more in migraineurs versus controls 13 .…”
mentioning
confidence: 89%